Evaluasi Kebijakan Kepala Madrasah dalam Meningkatkan Profesionalitas Guru MAS Al- Manshuriyah - Selamat Tulipri; Rahmat Hidayat; Hamengkubuwono Hamengkubuwono; Jumira Warlizasusi (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study was to study the evaluation of the headmaster in improving the professionalism of MAS Al-Manshuriyah teachers. This research is a type of qualitative research consisting of research that produces descriptive data in the form of written or oral data from people and published. The form of the research is descriptive, that is the research conducted only to describe the state or status of a particular phenomenon. The results of the study, evaluation of the principal's policy in increasing the professionalism of teachers in carrying out their important tasks, appropriate policy considerations, will have an impact on improving the quality of teachers in carrying out their duties properly, but if the policies made are less precise, it will have an impact on improving the quality of teachers in carry out their duties properly. Conclusion, the principal's policy in increasing professional teachers in carrying out their duties went well, but there are some things that need to be updated, as well as policies that can be carried out properly, namely giving appropriate approval, the role of school supervisors and deliberations in relation to changes policies in improving teacher professionalism in carrying out their main tasks and functions properly Keywords: Policy Evaluation, Professionalism